2004
DOI: 10.1111/j.1365-2249.2004.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D is up-regulated in inflammatory bowel disease macrophages

Abstract: SUMMARYDown-regulation of receptors involved in the recognition or transmission of inflammatory signals and a reduced responsiveness support the concept that macrophages are 'desensitized' during their differentiation in the intestinal mucosa. During inflammatory bowel disease (IBD) intestinal macrophages (IMACs) change to a reactive or 'aggressive' type. After having established a method of isolation and purification of IMACs, message for cathepsin D was one of the mRNAs we found to be up-regulated in a subtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…In breast cancer, cathepsin D is overexpressed from 2-to 50-fold compared with its concentration in other cell types such as fibroblasts or normal mammary glands (15). Up-regulated cathepsin D has also been detected in the inflammatory setting (16). The role of cathepsin D may make it a possible biomarker for diagnosis and prognosis of some cancers; however, the data in this study suggest that it is also up-regulated in chronic pancreatitis, limiting its use as biomarker for pancreatic cancer.…”
Section: Validation Of Proteins That Are Overexpressed In Both Pancrementioning
confidence: 99%
“…In breast cancer, cathepsin D is overexpressed from 2-to 50-fold compared with its concentration in other cell types such as fibroblasts or normal mammary glands (15). Up-regulated cathepsin D has also been detected in the inflammatory setting (16). The role of cathepsin D may make it a possible biomarker for diagnosis and prognosis of some cancers; however, the data in this study suggest that it is also up-regulated in chronic pancreatitis, limiting its use as biomarker for pancreatic cancer.…”
Section: Validation Of Proteins That Are Overexpressed In Both Pancrementioning
confidence: 99%
“…Moreover, the cellular infiltration and proliferation of macrophages and gliosis have been reported to occur at the injury site in rat spinal cords with a clip compression injury [8]. Cathepsin D expression increases in the macrophages observed in many inflammatory diseases, including inflammatory bowel disease [6], testicular ischemia/reperfusion injury [7] and chronic obstructive pulmonary disease [4]. In rat spinal cords with autoimmune inflammation, cathepsin D is expressed in the infiltrating macrophages [11].…”
Section: Immunohistochemical Localization Of Cathepsin D In Rat Scimentioning
confidence: 99%
“…Although it has been known that normal intestinal macrophages show low proinflammatory activity, it has been shown that in intestinal diseases, particularly in CD, their profile differs considerably [13]. Indeed, these cells showed increased expression of co-stimulatory receptors, Toll-like receptors and inflammatory cytokines [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood monocytes have been divided into three distinct subsets according to CD14 and CD16 marker expression [18,20,21] + monocyte subsets, particularly the intermediate subset, have been associated with inflammatory functions [20] and are known to be the major producers of inflammatory cytokines such as TNF and interleukin (IL)-1β [22,23]. It was reported that, in CD patients with active disease, CD16…”
Section: Introductionmentioning
confidence: 99%